The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.5547/issn0195-6574-ej-vol20-no3-3
|View full text |Cite
|
Sign up to set email alerts
|

Why Has the Energy-Output Ratio Fallen in China?

Abstract: In China, between 1978 and 1995, energy use per unit of GDP fell by 55%. There has been considerable debate about the major factors responsible for this dramatic decline in the energyoutput ratio. In this paper we use the two most recent input-output tables to decompose the reduction in energy use into technical change and various types of structural change, including changes in the quantity and composition of imports and exports. In performing our analysis we are forced to deal with a number of problems with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(117 citation statements)
references
References 9 publications
6
109
1
1
Order By: Relevance
“…7 There is a wide suspicion that the official rate of inflation for producer prices is understated because the official prices might not be the properly weighted average of plan and market prices, might have been misreported, or were not produced using a good sample of firms (Rawski, 1991;Garbaccio et al, 1999). Assuming that the official data for GDP and industrial subsector value added are correct, lowering the annual growth rate of each industrial subsector by 2% is equivalent to raising the annual rate of inflation of all industrial products by the same percentage in terms of the impacts on the energy consumption, although the reasons for the two adjustments are very different from each other.…”
Section: Discussionmentioning
confidence: 99%
“…7 There is a wide suspicion that the official rate of inflation for producer prices is understated because the official prices might not be the properly weighted average of plan and market prices, might have been misreported, or were not produced using a good sample of firms (Rawski, 1991;Garbaccio et al, 1999). Assuming that the official data for GDP and industrial subsector value added are correct, lowering the annual growth rate of each industrial subsector by 2% is equivalent to raising the annual rate of inflation of all industrial products by the same percentage in terms of the impacts on the energy consumption, although the reasons for the two adjustments are very different from each other.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as has been argued by Fisher-Vanden et al (2004), sectorial changes can be important to explain the decline in energy intensity. However, most previous studies have found sectoral shift to be a relatively small contributor to the decline in China's energy intensity (Garbaccio et al, 1999;Liao et al, 2007, andMa andStern, 2008). 10…”
Section: Literature Reviewmentioning
confidence: 99%
“…The objective of these papers, which include among others Kambara (1992), Garbaccio et al (1999), Chu at al. (2006), is to investigate the explanation for such decline in energy intensity.…”
Section: Literature Reviewmentioning
confidence: 99%